Clinical Cases in Psoriasis - Wu, Jashin J. (Springer International Publishing : Imprint: Springer, 2017)
This title recognises that clinical cases are a key component in modern medical education, assisting the trainee or recertifying clinician to work through unusual cases using best practice techniques. It also acknowledges that psoriasis is an important discipline in this regard since it is a highly visual subject requiring the reader to describe often very subtle differences in the presentation of patients and define accurately the diagnostic and management criteria to base their clinical decision-making on. The objective of this book is to provide readers with an overview of the diagnosis and multidisciplinary management of psoriasis. As part of the Clinical Cases in Dermatology series, the range of titles cover the most common skin problems encountered in clinical practice and many of the rarer diseases that may be encountered by the practicing dermatologist.
Keywords: Medicine.; Dermatology.; elektronické knihy; electronic books